Pengaruh Komunikasi Interpersonal pada Kinerja Organisasi : Sebuah Meta-Analisis - Rahmi Wahyuni (Journal Of Administration and Educational Management (ALIGNMENT), 2024)
This research investigates the significant impact of interpersonal communication on overall organizational performance. This type of research is meta-analysis research. Inclusion criteria in research are research from national or international journals indexed by SINTA and Scopus, research related to personal communication on organizational performance, research published in 2020-2024, and attaching complete data in analyzing the effect size value. This analysis includes a comprehensive review of the existing literature on this topic, spanning various industries and organizational settings. The meta-analysis results show a strong positive influence between interpersonal communication and organizational performance with a value of rES=0.818; z= 0.629; p < 0.001) with a high effect size category. Furthermore, this research reveals that effective interpersonal communication can increase team member engagement, improve collaboration, and improve problem-solving skills, ultimately leading to better organizational outcomes. In conclusion, there is a positive influence between personal communication on organizational performance Keywords: Interpersonal Communication, Meta-analysis, Organizational performance